Servants of Satan : the age of the witch hunts - Klaits, Joseph (Indiana University Press, 1985)
This is the first book to consider the general course and significance of the European witch craze of the sixteenth and seventeenth centuries since H.R. Trevor-Roper's classic and pioneering study appeared some fifteen years ago. Drawing upon the advances in historical and social-science scholarship of the past decade and a half, Joseph Klaits integrates the recent appreciations of witchcraft in regional studies, the history of popular culture, anthropology, sociology, and psychology to better illuminate the place of witch hunting in the context of social, political, economic and religious cha.